2019
DOI: 10.3390/cancers11111811
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating Effect of 1-Palmitoyl-2-Linoleoyl-3-Acetyl-Rac-Glycerol (PLAG) on a Murine Model of 5-Fluorouracil-Induced Hematological Toxicity

Abstract: 5-Fluorouracil (5-FU) is an antimetabolite chemotherapy widely used for the treatment of various cancers. However, many cancer patients experience hematological side effects following 5-FU treatment. Here, we investigated the protective effects of 1-palmitoyl-2-linoleoyl-3-acetyl-rac-glycerol (PLAG) as a mitigator against 5-FU-induced hematologic toxicity, including neutropenia, monocytopenia, thrombocytopenia, and thrombocytosis, in Balb/c mice injected with 5-FU (100 mg/kg, i.p.). Administration of PLAG sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 60 publications
2
1
0
Order By: Relevance
“…In agreement with other studies, ~ 40% depletion of the ability of monocyte/macrophage cells to proliferate after treatment by 5-FU has been observed (Fig. 6F) (VanderVeen et al 2020;Jeong et al 2019;Farhat et al 2014). Interestingly, after the addition of our polymeric systems to the THP-1 cells, increased proliferation was noted (Fig.…”
Section: Biological Studiessupporting
confidence: 92%
“…In agreement with other studies, ~ 40% depletion of the ability of monocyte/macrophage cells to proliferate after treatment by 5-FU has been observed (Fig. 6F) (VanderVeen et al 2020;Jeong et al 2019;Farhat et al 2014). Interestingly, after the addition of our polymeric systems to the THP-1 cells, increased proliferation was noted (Fig.…”
Section: Biological Studiessupporting
confidence: 92%
“…50 Interestingly, different from human modeling, it has been demonstrated that 5-FU induces a moderate reduction of platelet counts (thrombocytopenia), followed by a profound and prolonged increase of platelet counts (thrombocytosis) in mice, and thrombocytosis could result in increased risks of thrombosis. 51,52 In this work, we found that 5-FU caused an increase in platelets in mice after administration, which was consistent with the above literature reports, and at the same time, we also found that LipoXL-01 caused neither thrombocytopenia nor thrombocytosis, suggesting LipoXL-01 had less effect on platelets.…”
Section: Transmission Electron Microscope (Tem)supporting
confidence: 92%
“…Therefore, we think that CXCL8 is also a good therapeutic target for the treatment of gouty inflammation. In addition, there were no reports of toxicity or adverse effects when high doses of PLAG were administered in the non-clinical toxicity test (49,66). Since PLAG is delivered via oral administration, it has an advantage in the way of drug delivery than other gout drugs.…”
Section: Discussionmentioning
confidence: 99%